Analisis Miskonsepsi Operasi Penjumlahan Pecahan Siswa SD Kelas 5 Nisam Antara Aceh Utara - Asmaul Husna; Rahmat; Bahri, Samsul; Safira, Suci Aulia (Tadris Matematika, 2024)
The purpose of this study was to determine the misconceptions of 5th-grade students in solving fraction addition problems. This type of research is descriptive qualitative. The research sample consisted of 30 grade 5 students in elementary schools in Nisam Antara sub-district, North Aceh. Students were selected based on the characteristics of moderate and low ability levels. To obtain data, through tests and interviews with each research subject. Based on the results of the study, there are several misconceptions in solving problems about fraction addition operations, namely: 1) students' inability to understand the concept of fraction addition, 2) teachers' informal way of teaching and presentation of teaching materials that pay less attention to student involvement, 3) lack of motivation level, response and focus of students when learning fraction addition operation and, 4) lack of understanding of prerequisite material of fraction addition operation, 5) students who have not been able to equalize the denominator, and do not know the concept of fraction addition operation.